(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2016)
A sirenian rib has been recovered at Motta San Giovanni (Reggio Calabria) in the “Floresta Calcarenites”, a Formation cropping out in Sicily and Calabria and dated late Burdigalian-Langhian. Although the rib is not a diagnostic bone for taxonomy, its presence in southern Calabria extends the knowledge about the paleobiogeography of the Family Dugongidae in the Mediterranean basin. The find is hitherto the only record of sirenians in the Floresta calcarenites. Moreover, the specimen extends back to the Early-Middle Miocene (late Burdigalian-Langhian) the occurrence of sirenians in Calabria, previously determined thanks to substantial material from the Late Miocene (Tortonian) of the Monte Poro area (Vibo Valentia). The paleoenvironment of the Floresta calcarenites was a warm and shallow sea, consistent with the paleoecology of Dugongidae.